A method for preparing battery-grade iron phosphate using iron resources in ilmenite
Through the preparation method of iron resources in ilmenite, and the technology of pre-neutralization of lime and calcium dihydrogen phosphate, the problem of difficult utilization of iron resources in waste acid in titanium dioxide production in the sulfuric acid method is solved, and efficient iron resource recovery and high-quality production of iron phosphate are achieved.
Patent Information
- Application Number
- CN202310289676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-23
AI Technical Summary
During the titanium dioxide production process of sulfuric acid, it is difficult to achieve resource utilization of iron resources in waste acid, resulting in waste of iron resources and unclean production process.
The method of preparing battery-grade hydrated iron phosphate by ilmenite is adopted to pre-neutralize titanium dioxide waste acid by lime, purify the by-product ferrous sulfate, and use calcium dihydrogen phosphate to achieve the conversion and precipitation of ferrous sulfate to synthesize high-quality hydrated iron phosphate.
It realizes efficient utilization of iron resources in titanium dioxide waste acid, reduces iron source costs, avoids the production of titanium red gypsum, improves the crystallinity and purity of iron phosphate, and meets the requirements of battery-grade iron phosphate.
Smart Images

Figure CN116281920B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing battery-grade iron phosphate, in particular to a method for preparing battery-grade hydrated iron phosphate by utilizing iron resources in ilmenite, and belongs to the technical field of resource utilization of titanium dioxide waste acid. Background Art
[0002] The sulfuric acid process titanium dioxide technology uses ilmenite as raw material. Every 1.0 ton of titanium dioxide produced will bring in about 0.80 tons of Fe resources, which are distributed in ferrous sulfate heptahydrate (accounting for 65% of the total Fe) and titanium dioxide waste acid (accounting for 35% of the total Fe). There are reports that the iron resources in ferrous sulfate heptahydrate slag are used to prepare battery-grade iron phosphate, and the iron resources in waste acid enter titanium gypsum with lime neutralization and cannot be used. There are no reports on the technology of preparing battery-grade iron phosphate using ferrous sulfate heptahydrate and iron resources in waste acid.
[0003] There are three methods for preparing ferric phosphate: solid phase sintering, hydrothermal method and chemical precipitation method. The main method for large-scale industrial application is chemical precipitation method. The chemical precipitation method is to mix the iron source and the phosphorus source evenly, generate hydrated ferric phosphate precipitate by adjusting the pH value of the reaction system, calcine to remove the crystal water, and obtain anhydrous ferric phosphate product. The iron sources mainly include free iron (such as iron powder, iron filings) and ferrous sulfate. The sulfuric acid process titanium dioxide produces a large amount of iron resources. The iron resources in ilmenite (including ferrous sulfate heptahydrate and iron resources in waste acid) are fully utilized to prepare battery-grade iron phosphate, which can not only greatly reduce the cost of iron sources, but also convert the iron resources in waste acid into iron phosphate, avoiding the production of titanium red gypsum, which is conducive to the clean production of sulfuric acid process titanium dioxide technology. Summary of the invention
[0004] In view of the technical problems in the prior art that it is difficult to realize resource production of iron resources in waste acid during the production of titanium dioxide by sulfuric acid method, the purpose of the present invention is to provide a method for preparing battery-grade hydrated iron phosphate using iron resources in ilmenite. The method uses ferrous sulfate, a by-product produced in the process of titanium dioxide by sulfuric acid method, and iron resources in waste acid as iron sources to obtain battery-grade iron phosphate. More specifically, lime is first used to neutralize most of the free acid in the waste acid, and then the pH is slowly adjusted by neutralization with iron powder to precipitate and remove aluminum and titanium. After the aluminum and titanium are removed, calcium dihydrogen phosphate is used as the phosphorus source in the liquid, and hydrated iron phosphate is synthesized by homogeneous precipitation technology. Battery-grade anhydrous iron phosphate is obtained by heat treatment to remove crystal water. The iron phosphate prepared by this method has high crystallinity, and the iron-phosphorus content, tap density, impurity element content, etc. all meet the requirements of battery-grade iron phosphate.
[0005] In order to achieve the above technical objectives, the present invention provides a method for preparing battery-grade iron phosphate using iron resources in ilmenite, which comprises the following steps:
[0006] 1) Pre-neutralizing titanium dioxide waste acid with lime slurry to obtain gypsum slag and pre-neutralized liquid;
[0007] 2) Add iron powder to the pre-neutralized solution to neutralize and hydrolyze Al 3+ and Ti 3+ , obtaining a purified ferrous sulfate solution;
[0008] 3) Adjust the pH value of the ferrous sulfate purification solution to <2, then add calcium dihydrogen phosphate and maintain the total phosphorus concentration in the ferrous sulfate purification solution ≤1.5 mol / L, and perform Ca 2+ The precipitation reaction is carried out for 1.0 to 3.0 hours to obtain calcium sulfate slag and ferrous dihydrogen phosphate solution;
[0009] 4) After adjusting the pH of the ferrous dihydrogen phosphate solution, first 2+ Oxidation, then Fe 3+ The hydrated ferric phosphate is precipitated by precipitation reaction, and the hydrated ferric phosphate is washed and dried to obtain the product.
[0010] In the method for preparing battery-grade iron phosphate using iron resources in ilmenite provided by the present invention, the key points of the technical solution are: first, the resource utilization of titanium dioxide waste acid is realized. The iron concentration in titanium dioxide waste acid is 40-50g / L, and the free sulfuric acid concentration is 90-120g / L. Titanium dioxide waste acid cannot directly use iron powder to remove titanium and aluminum, which will consume a large amount of iron powder. The use of lime to pre-neutralize the excess free acid in titanium dioxide waste acid can not only convert sulfuric acid into gypsum slag for open-circuit removal, effectively reducing the consumption of iron powder in the iron powder neutralization and Ti / Al removal stage, reducing costs, and controlling the endpoint pH within a suitable range, which is conducive to the subsequent dissolution of ferrous sulfate and iron powder impurity removal process. Second, the use of iron powder to neutralize the H of the reaction system + To control the pH value, in order to efficiently purify and remove Ti in the solution 3+ / Al 3+ During the process, Fe 2+ Oxidized to Fe 3+ , thereby improving the recovery rate of iron resources. On the third hand, in the process of using calcium dihydrogen phosphate to convert ferrous sulfate into ferrous dihydrogen phosphate, calcium ions are likely to remain in the ferrous dihydrogen phosphate, and the calcium ions are difficult to remove by conventional methods in the subsequent process. By strictly controlling the pH, temperature, time and total phosphorus concentration and other conditions during the precipitation reaction, the coordinated control of these conditions can precipitate the calcium ions in the ferrous dihydrogen phosphate solution with high selectivity and efficiency, and the calcium ion precipitation efficiency reaches more than 95%, thereby obtaining a ferrous dihydrogen phosphate solution with a low calcium ion concentration. The small amount of residual calcium ions can control the reaction conditions during the oxidation reaction so that it is mainly present in the filtrate in the form of ions and removed. On the fourth hand, by synthesizing hydrated ferric phosphate under relatively high acidity conditions (pH of 0 to 1.5), it can effectively prevent the coexistence of Ca in the initial stage of its synthesis. 2+ Mg 2+ , Mn2+ The impurity components such as H2PO4 form phosphate precipitates, and as the reaction progresses, - Converted to FePO4·2H2O to release H + , further increasing the acidity of the reaction system and also being beneficial for dissolving the Ca2+ entrained in the hydrated iron phosphate. 2+ Mg 2+ , Mn 2+ Impurity components such as ferric phosphate and hydrated ferric phosphate are removed to ensure the purity of the hydrated ferric phosphate product.
[0011] As a preferred solution, the endpoint pH of the pre-neutralization is 1.0 to 2.0, and the endpoint pH of the pre-neutralization is further preferably 1.2 to 1.5. Most of the sulfuric acid in the titanium dioxide waste acid can be converted into gypsum by pre-neutralization to achieve an open circuit, which can effectively reduce the loss of iron powder in the subsequent iron powder neutralization process, and the control of the pre-neutralization pH is conducive to the dissolution process of the by-product diferric phosphate and the dissolution and impurity removal process of the iron powder.
[0012] As a preferred solution, by-product ferrous sulfate heptahydrate is added to the pre-neutralized liquid to ensure that the Fe concentration in the purified ferrous sulfate liquid is 70-120 g / L. The iron concentration in the titanium dioxide waste acid is 40-50 g / L, and the by-product ferrous sulfate heptahydrate can be further used as an iron source to achieve comprehensive utilization of the iron resources in the by-product ferrous sulfate heptahydrate and waste acid in the sulfuric acid process titanium dioxide production process.
[0013] As a preferred embodiment, the neutralization and hydrolysis precipitation of Al 3+ and Ti 3+ The end point pH is 3.5 to 6, and preferably neutralization and hydrolysis precipitation of Al 3+ and Ti 3+ The end point pH is 4.0-5.0. Controlling the pH value at the end point of the neutralization hydrolysis precipitation reaction is beneficial to improving the hydrolysis precipitation efficiency of titanium and aluminum.
[0014] As a preferred embodiment, the neutralization and hydrolysis precipitation of Al 3+ and Ti 3+ The temperature is 60-90°C and the time is 5-24 hours. Under the preferred neutralization conditions, it is beneficial to promote the precipitation process of titanium and aluminum. 3+ and Ti 3+ The temperature is more preferably 70 to 80° C., and the time is more preferably 6 to 8 hours.
[0015] As a preferred solution, the calcium dihydrogen phosphate is added uniformly or slowly in multiple batches. If calcium dihydrogen phosphate is added too quickly, the local alkali concentration of the solution is easily too high, and the concentration of divalent iron ions in the solution is too high, which is easily oxidized to generate iron hydroxide and calcium sulfate to be precipitated together. The multiple batches are 5 to 10 batches.
[0016] As a preferred solution, the phosphorus / iron molar ratio of the monocalcium phosphate and the ferrous sulfate in the ferrous sulfate purification solution is 1.0 to 1.2. When the phosphorus / iron molar ratio is further increased, the calcium ion precipitation efficiency will be reduced, and the phosphorus and iron loss rate will also increase. The phosphorus / iron molar ratio of the monocalcium phosphate and the ferrous sulfate in the ferrous sulfate purification solution is further preferably 1.05 to 1.15.
[0017] As a preferred solution, the ferrous dihydrogen phosphate solution is adjusted to pH = 0-1.5, more preferably 0.6-1.2. By synthesizing hydrated ferric phosphate under high acidity conditions, it is possible to effectively prevent the coexistence of Ca in the solution system. 2+ Mg 2+ , Mn 2+ Impurity components such as phosphate precipitate.
[0018] As a preferred embodiment, the Fe 2+ During the oxidation process, hydrogen peroxide is used as an oxidant, the amount of hydrogen peroxide in the hydrogen peroxide is 1.0 to 1.2 times the theoretical molar amount required to convert divalent iron into trivalent iron, the temperature is 40 to 80° C., and the time is 1 to 3 hours.
[0019] As a more preferred solution, the Fe 3+ During the precipitation reaction, the temperature is 85-95°C and the time is 6-20 hours.
[0020] By synergistically controlling Fe 3+ The pH, temperature and other conditions during the precipitation reaction can not only effectively prevent metal ion impurities from entering the crystals of hydrated iron phosphate, but also regulate the crystal growth process of lithium iron phosphate to obtain high tap density hydrated iron phosphate with high particle size and crystallinity.
[0021] The iron concentration in the titanium dioxide waste acid involved in the present invention is 40-50 g / L, and the free sulfuric acid concentration is 90-120 g / L. The free sulfuric acid concentration in the titanium dioxide waste acid is relatively high.
[0022] The mass percentage concentration of the lime slurry of the present invention is in the range of 5 to 25%.
[0023] The present invention uses a dilute sulfuric acid solution to adjust the pH, which is obtained by diluting concentrated sulfuric acid and water in a volume ratio of 1:1 to 1:4.
[0024] The hydrogen peroxide of the invention is industrial hydrogen peroxide with a mass percentage concentration of 30%.
[0025] The present invention provides a method for preparing battery-grade iron phosphate using iron resources in ilmenite, comprising the following four steps:
[0026] (1) Lime pre-neutralization process of titanium dioxide waste acid: Lime is prepared into a slurry with a concentration of 5-25%, and is slowly added to the titanium dioxide waste acid (specific components are shown in Table 1) in batches for pre-neutralization. The pH of the system is adjusted to 1.0-2.0. After the reaction reaches the end point, solid-liquid separation is performed to obtain gypsum and pre-neutralized liquid.
[0027] (2) Iron preparation - neutralization, hydrolysis and precipitation to remove Ti 3+ / Al 3+ Process: Add a certain amount of ferrous sulfate heptahydrate (specific composition see Table 2) to the pre-neutralized solution, add iron powder to the solution, heat to 60-90°C, stir and react for 5-24h, control the pH of the reaction system to 3.5-6.0, stop the reaction, and perform solid-liquid separation to obtain Ti removal product. 3+ / Al 3+ The post-liquid is also called ferrous sulfate purified liquid, and the Fe concentration is 70-120g / L.
[0028] (3) Preparation process of ferrous dihydrogen phosphate solution: add dilute sulfuric acid solution to the purified ferrous sulfate solution to adjust the pH to <2, then add calcium dihydrogen phosphate and maintain the total phosphorus concentration in the purified ferrous sulfate solution ≤1.5 mol / L, carry out precipitation reaction at 60-80°C for 1.0-3.0h, and carry out solid-liquid separation after the reaction reaches the end point to obtain calcium sulfate slag and ferrous dihydrogen phosphate solution;
[0029] (4) Synthesis process of hydrated iron phosphate: add dilute sulfuric acid solution to the ferrous dihydrogen phosphate solution to adjust the pH to 0-1.5, and slowly add hydrogen peroxide at room temperature to oxidize Fe 2+ , oxidize at 40-80℃ for 1-3h, then raise the system temperature to 85-95℃ and keep the temperature constant for 6-20h to precipitate Fe 3+ Prepare hydrated iron phosphate, after the reaction reaches the end point, separate the solid and liquid and wash with water until no SO4 is detected in the washing water 2- , and drying the solid in a constant temperature drying oven to obtain a hydrated iron phosphate product.
[0030] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0031] (1) The by-product ferrous sulfate heptahydrate is dissolved by using the pre-neutralized solution of titanium dioxide waste acid, which realizes the coordinated utilization of iron resources in ilmenite (iron in titanium dioxide waste acid and ferrous sulfate slag). At the same time, because the Fe in titanium dioxide waste acid is converted into hydrated iron phosphate, SO4 in the system is ensured. 2- The switch to white gypsum, which has a large market capacity, avoids the precipitation of Fe in waste acid to form titanium red gypsum, which leads to large-scale stockpiling and causes environmental pollution and waste of resources.
[0032] (2) The whole process uses Ca 2+ System (pre-neutralization of waste acid using lime, precipitation of Fe3+ The phosphorus source is calcium dihydrogen phosphate), which can ensure that SO4 2- By converting it into white gypsum, which has a wide market share, the existing wastewater treatment facilities of sulfuric acid-process titanium dioxide enterprises can be fully utilized. There is no need to build or add new equipment, which greatly saves the construction and operation costs of environmental protection facilities required for hydrated iron phosphate.
[0033] (3) In the process of using calcium dihydrogen phosphate to convert ferrous sulfate into ferrous dihydrogen phosphate, by strictly controlling the conditions such as pH, temperature, time and total phosphorus concentration during the precipitation reaction, the coordinated control of these conditions can make it possible to precipitate calcium ions in the ferrous dihydrogen phosphate solution with high selectivity and high efficiency, and the calcium ion precipitation efficiency reaches more than 95%, thereby obtaining a ferrous dihydrogen phosphate solution with a very low calcium ion concentration. The small amount of residual calcium ions can be removed by controlling the reaction conditions during the oxidation reaction so that it is mainly present in the filtrate in the form of ions, thereby avoiding a high amount of residual calcium ions in lithium iron phosphate doping.
[0034] (4) The prepared iron phosphate has a high degree of crystallinity, and the iron-phosphorus content, tap density, and impurity element content all meet the requirements of battery-grade iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The XRD diagrams of the ferric phosphate products of Examples 7 to 12 show that the XRD spectra of the ferric phosphate products are basically consistent with the standard card FePO4﹒2H2O-PDF﹒ #760451, and there is no impurity peak.
[0036] Figure 2 This is the SEM of the iron phosphate product of Example 7.
[0037] Figure 3 This is the SEM of the iron phosphate product of Example 10.
[0038] Figure 2 and Figure 3 It can be seen that the iron phosphate product has a uniform layered microstructure, with multiple microsheets agglomerated to form a single aggregate with a particle size of 3 to 10 μm. DETAILED DESCRIPTION
[0039] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following implementation modes are combined with the accompanying drawings for explanation. The following embodiments are not intended to further limit the protection scope of the claims of the present invention.
[0040] The chemical reagents involved in the following examples are conventional commercially available products unless otherwise specified.
[0041] Example 1
[0042] 100 mL of titanium dioxide waste acid (specific components are shown in Table 1), 13.0 g of calcium oxide is weighed and prepared into 15% lime slurry, and the lime slurry is slowly added to the titanium dioxide waste acid with a separatory funnel, and mechanical stirring is performed while adding. After the addition is completed, the reaction is continued at room temperature for 2 hours, and the reaction end point pH is measured to be 1.3, and then the solid-liquid separation is performed, and the obtained filter residue is the gypsum product, and the filtrate is the neutralized liquid. The element composition of the neutralized liquid and the quality of gypsum are shown in Table 3.
[0043] Example 2
[0044] 100 mL of titanium dioxide waste acid (specific components are shown in Table 1), 13.5 g of calcium oxide is weighed and prepared into a 15% lime slurry, and the lime slurry is slowly added to the titanium dioxide waste acid with a separatory funnel, and mechanical stirring is performed while adding. After the addition is completed, the reaction is continued at room temperature for 2 hours, and the reaction end point pH is measured to be 1.2, and then the solid-liquid separation is performed. The filter residue obtained is the gypsum product, and the filtrate is the neutralized liquid. The element composition of the neutralized liquid and the quality of gypsum are shown in Table 3.
[0045] Example 3
[0046] 5000mL of titanium dioxide waste acid (specific components are shown in Table 1), 700.0g of calcium oxide is weighed and configured into 15% lime slurry, and the lime slurry is slowly added to the titanium dioxide waste acid with a separatory funnel, and mechanical stirring is performed while adding. After the addition is completed, it is allowed to continue to react at room temperature for 2h, and the reaction end point pH is measured to be 1.4, and then the solid-liquid separation is performed, and the obtained filter residue is the gypsum product, and the filtrate is the neutralized liquid. The element composition of the neutralized liquid and the quality of gypsum are shown in Table 3.
[0047] Example 4
[0048] 700 mL of the neutralized solution of Example 3 was measured, 201 g of the by-product ferrous sulfate slag was added, and the solution was stirred at room temperature for 30 min until it was dissolved. After dissolution, it was placed in a water bath at 85°C for constant temperature, and then 9.5 g of iron powder with a mass fraction of 98% was added. The reaction was continued to be stirred for 8 h, and the pH value of the reaction end point was measured to be 4.35. The solid-liquid separation was performed to obtain aluminum removal slag and ferrous sulfate purified liquid. The composition of the ferrous sulfate purified liquid is shown in Table 4.
[0049] Example 5
[0050] 700 mL of the neutralized solution of Example 3 was measured, 201 g of the by-product ferrous sulfate slag was added, and the solution was stirred at room temperature for 30 min until it was dissolved. After dissolution, it was placed in a water bath at 70° C. and kept at a constant temperature. Then 10.4 g of iron powder with a mass fraction of 98% was added, and the reaction was continued to be stirred for 20 h. The pH value at the end point of the reaction was measured to be 4.65, and the solid-liquid separation was performed to obtain aluminum removal slag and ferrous sulfate purified liquid. The composition of the ferrous sulfate purified liquid is shown in Table 4.
[0051] Example 6
[0052] 1200 mL of the neutralized solution of Example 3 was measured, 345 g of the by-product ferrous sulfate slag was added, and the solution was stirred at room temperature for 30 min until it was dissolved. After dissolution, it was placed in a water bath at 80° C. and kept at a constant temperature. Then 15.6 g of iron powder with a mass fraction of 98% was added, and the reaction was continued to be stirred for 16 h. The pH value at the end point of the reaction was measured to be 4.58, and the solid-liquid separation was performed to obtain aluminum slag and ferrous sulfate purified liquid. The composition of the ferrous sulfate purified liquid is shown in Table 4.
[0053] Comparative Example 1
[0054] 700 mL of the neutralized solution of Example 3 was taken, and except that the amount of iron powder added was 7.0 g, the other conditions were the same as those of Example 4. After the reaction was completed, the end point pH was measured to be 3.05. The composition of the purified ferrous sulfate solution and the removal rate of impurity elements are shown in Table 4.
[0055] Comparative Example 2
[0056] 700 mL of the neutralized solution of Example 3 was taken, and the reaction time was 30 min, and the other conditions were the same as those of Example 4. After the reaction was completed, the end point pH was measured to be 2.08. The composition of the purified ferrous sulfate solution and the removal rate of impurities are shown in Table 4.
[0057] Example 7
[0058] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 6 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and determine the pH of the filtrate. ICP analysis shows that the Ca precipitation rate is 96.80%, the Fe loss rate is 0.09%, and the P loss rate is 0.94%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 1.2, transfer 5.5 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for constant temperature reaction for 12 h. When Fe 3+ When the concentration is 1.5 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0059] Example 8
[0060] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and determine the pH of the filtrate. ICP analysis shows that the Ca precipitation rate is 95.50%, the Fe loss rate is 0.12%, and the P loss rate is 0.97%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 1.2, transfer 6.3 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for 12 h. When the reaction system contains Fe 3+ When the concentration is 1.3 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0061] Example 9
[0062] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and determine the pH of the filtrate. ICP analysis shows that the Ca precipitation rate is 95.25%, the Fe loss rate is 0.05%, and the P loss rate is 0.99%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 1.2, transfer 7 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for 12 h. When Fe 3+ When the concentration is 1.2 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0063] Example 10
[0064] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and determine the pH of the filtrate. ICP analysis shows that the Ca precipitation rate is 98.70%, the Fe loss rate is 0.15%, and the P loss rate is 0.11%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 0.9, transfer 5.5 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for 12 h. When Fe 3+ When the concentration is 1.0 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0065] Embodiment 11
[0066] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and measure the pH of the filtrate. ICP analysis shows that the Ca precipitation rate is 95.80%, the Fe loss rate is 0.08%, and the P loss rate is 0.92%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 0.9, transfer 6.3 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for 12 h. When Fe 3+ When the concentration is 1.8 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0067] Example 12
[0068] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches, stir at a constant temperature of 70°C for 2.0 h, and perform solid-liquid separation after the reaction reaches the endpoint to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and determine the pH of the filtrate. ICP analysis showed that the Ca precipitation rate was 96.77%, the Fe loss rate was 0.13%, and the P loss rate was 0.12%. Use dilute sulfuric acid to adjust the pH of the pre-synthesis liquid to 0.9, transfer 7 mL of 30% hydrogen peroxide, and slowly add it dropwise to the pre-synthesis liquid. After the addition is complete, react at 50°C for 60 min, and then place it in a water bath at 95°C for 12 h. When the reaction system contains Fe 3+ When the concentration is 1.2 g / L, the reaction is stopped, vacuum filtration and washing are performed until no sulfate ions are detected in the barium chloride solution, the wet weight of the product is weighed, and the product is dried in a constant temperature drying oven at 100°C and the dry weight is weighed, and the content of each element in the product is analyzed. The content of each main component and impurity element in the product is shown in Table 5.
[0069] Comparative Example 3
[0070] 100 mL of the purified ferrous sulfate solution of Example 6 was measured. In the process of preparing the ferrous dihydrogen phosphate solution, except that the pH was adjusted to 3.0, the other conditions were the same as those of Example 11. After the reaction reached the end point, solid-liquid separation was performed to obtain a gypsum product and a pre-synthesis liquid. The slag weight and the filtrate volume were measured respectively, and the filtrate pH was measured. ICP analysis showed that the Ca precipitation rate was 88.05%, the Fe loss rate was 65.89%, and the P loss rate was 54.86%. As can be seen from the results, the iron and phosphorus loss rates are relatively high.
[0071] Comparative Example 4
[0072] Measure 100 mL of the purified ferrous sulfate solution of Example 6, add 23.3 g of calcium dihydrogen phosphate evenly in 8 batches according to the P / Fe ratio of 1.2, stir at 70 ° C for 2.0 h, and perform solid-liquid separation after the reaction reaches the end point to obtain a gypsum product and a pre-synthesis liquid. Measure the slag weight and the filtrate volume, and measure the filtrate pH. ICP analysis shows that the Ca precipitation rate is 90.89%, the Fe loss rate is 2.15%, and the P loss rate is 2.03%. In the subsequent synthesis of iron phosphate, except that the pH of the pre-synthesis liquid is adjusted to 3.0, the other conditions are the same as in Example 12. The contents of each main component and impurity element in the product are shown in Table 5.
[0073] Comparative Example 5
[0074] The experiment was carried out according to the steps in Example 12, except that the reaction temperature was adjusted to 50°C. After the reaction was continued at constant temperature for 12 hours, it was observed that no precipitate was generated.
[0075] Comparative Example 6
[0076] The experiment was carried out according to the steps in Example 12, except that the P / Fe of the reaction was adjusted to 0.8. After the reaction was carried out at a constant temperature for 12 hours, no precipitate was observed to be generated.
[0077] Table 1 ICP analysis results of titanium dioxide waste acid
[0078]
[0079]
[0080] Table 2 ICP analysis results of by-product ferrous sulfate slag
[0081] element Content (wt.%) element Content (wt.%) Fe 17.2 Zn 0.0061 S 11.0 P 0.0006 Mg 0.33 Silic acid 0.0018 Mn 0.094 Ni 0.0041 Ti 0.18 Zr 0.0003 Al 0.0022 Co 0.0043 Na 0.0016 B 0.0002 Ca 0.0023 Sn 0.0002 V 0.0010 Pb 0.0001 Cr 0.0001 Li 0.0001 Cu 0.0001 Ba <0.0001
[0082] Table 3 Experimental results of lime pre-neutralization of titanium dioxide waste acid
[0083]
[0084] Table 4 Experimental results of impurity removal examples
[0085]
[0086]
[0087] Table 5 Physical and chemical properties test results of hydrated ferric phosphate
[0088]
Claims
1. A method for preparing battery-grade iron phosphate using iron resources in ilmenite, characterized in that: The following steps are involved: 1) Pre-neutralizing titanium dioxide waste acid with lime slurry to obtain gypsum slag and pre-neutralized liquid; the pre-neutralization endpoint pH=1~2; 2) Add iron powder to the pre-neutralized solution to neutralize and hydrolyze Al 3+ and Ti 3+ , obtaining a purified ferrous sulfate solution; 3) Adjust the pH value of the ferrous sulfate purification solution to <2, then add calcium dihydrogen phosphate and maintain the total phosphorus concentration in the ferrous sulfate purification solution ≤1.5mol / L, and precipitate Ca at 60~80℃. 2+ The reaction is carried out for 1.0 to 3.0 hours to obtain calcium sulfate slag and ferrous dihydrogen phosphate solution; the calcium dihydrogen phosphate is added in multiple batches evenly or slowly; 4) After adjusting the pH of the ferrous dihydrogen phosphate solution, first 2+ After oxidation, Fe 3+ The hydrated ferric phosphate is precipitated by precipitation reaction, and the hydrated ferric phosphate is washed and dried to obtain the product.
2. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The by-product ferrous sulfate heptahydrate is added to the pre-neutralized liquid to ensure that the Fe concentration in the purified ferrous sulfate liquid is 70-120 g / L.
3. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The neutralization and hydrolysis precipitation of Al 3+ and Ti 3+ The end point pH = 3.5 ~ 6.
0.
4. A method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1 or 3, characterized in that: The neutralization and hydrolysis precipitation of Al 3+ and Ti 3+ The temperature is 60~90℃ and the time is 5~24h.
5. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The phosphorus / iron molar ratio of the calcium dihydrogen phosphate and the ferrous sulfate in the ferrous sulfate purification solution is 1.00-1.
2.
6. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The ferrous dihydrogen phosphate solution is adjusted to pH = 0 ~ 1.
5.
7. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The Fe 2+ During the oxidation process, hydrogen peroxide is used as an oxidant, the amount of hydrogen peroxide in the hydrogen peroxide is 1.0 to 1.2 times the theoretical molar amount required to convert divalent iron into trivalent iron, the temperature is 40 to 80°C, and the time is 1 to 3 hours.
8. The method for preparing battery-grade iron phosphate using iron resources in ilmenite according to claim 1, characterized in that: The Fe 3+ During the precipitation reaction, the temperature is 85~95℃ and the time is 6~20h.
Citation Information
Patent Citations
Method for preparing ferric phosphate hydrate from titanium dioxide byproduct ferrous sulfate
CN111847416A
Method for preparing iron phosphate from iron-containing waste
CN115806279A